HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN ANAK USIA 4-5 TAHUN DI TKIT CAHAYA HATI KELURAHAN UTAN KAYU SELATAN - Ayu Inda Puspitasari, (2021)
The growth and development of children in Indonesia still needs more attention, the proportion of stunting is still relatively high, the rate of growth and development delays is still quite high, which is around 5-10% experiencing general developmental delays. Parenting patterns of parents become one of the factors on child development, because this parenting is one of the influencing factors on child development. The purpose of this study was to analyze the relationship of parents parenting patterns with the development of children aged 4-5 years in TKIT Cahaya Hati Utan Kayu Selatan Village. The method used is descriptive analytic with a total sampling technique of 35 mothers with children aged 4-5 years. Collecting data using a questionnaire via google form using the Parenting Style and Demention Questionnaire (PSDQ) and KPSP. The results of this study found that there was a the relationship of parents parenting patters with the development of children aged 4-5 years at TKIT Cahaya Hati, Utan Kayu Selatan Village with a p value = 0.001 (> = 0.05). Suggestions for further research is to conduct research with a wider population and parents to pay attention to the parenting applied to children and use quasi-experimental techniques to stimulate child development.